Complete PCB Design Using OrCAD® Capture and PCB Editor - Mitzner, Kraig, author 518225; Doe, Bob, author 648646; Akulin, Alexander, author 648647; Suponin, Anton, author 648648; Müller, Dirk, author 648649; ScienceDirect (Online service) 7722 (London : Academic Press, an imprint of Elsevier, 2019)
Complete PCB Design Using OrCAD Capture and PCB Editor, Second Edition, provides practical instruction on how to use the OrCAD design suite to design and manufacture printed circuit boards. Chapters cover how to Design a PCB using OrCAD Capture and OrCAD PCB Editor, adding PSpice simulation capabilities to a design, how to develop custom schematic parts, how to create footprints and PSpice models, and how to perform documentation, simulation and board fabrication from the same schematic design. This book is suitable for both beginners and experienced designers, providing basic principles and the program's full capabilities for optimizing designs.